2018
DOI: 10.1038/pr.2018.33
|View full text |Cite
|
Sign up to set email alerts
|

Surgical necrotizing enterocolitis in extremely premature neonates is associated with genetic variations in an intergenic region of chromosome 8

Abstract: BackgroundTwin studies suggest that genetic factors may account for up to 50% increased risk for necrotizing enterocolitis (NEC), but genome-wide association studies (GWAS) for NEC are lacking.MethodsGenotyping was done on Illumina BeadChip, followed by analysis using PLINK with logistic regression under an additive model.ResultsAmong 751 extremely low birth weight (<1000g, >401g) neonates, 30 had surgical NEC. 261 single nucleotide polymorphisms (SNPs) showed association with NEC at P<0.05, of which 35 were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Recent studies performed in twins have suggested that a genetic variation in an intergenic region of chromosome 8, labeled as the “NECRISK” region may be associated with increased risk for surgical NEC. Although no specific genes have been identified, pathway analyses have indicated possible pathways related to growth factor, calcium, and G-protein signaling, and others associated with inflammation that may contribute to NEC complications [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies performed in twins have suggested that a genetic variation in an intergenic region of chromosome 8, labeled as the “NECRISK” region may be associated with increased risk for surgical NEC. Although no specific genes have been identified, pathway analyses have indicated possible pathways related to growth factor, calcium, and G-protein signaling, and others associated with inflammation that may contribute to NEC complications [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of the contributing genetic factors, the association of mutations or single-nucleotide polymorphisms (SNPs) in individual genes with the incidence of NEC have been most investigated; reviewed by Cuna et al 3 Additionally, association between NEC with genome-wide SNPs and with organ-specific and gene-specific epigenetic changes have been analyzed, which have been summarized in other reviews in this issue. [4][5][6] Numerical Chromosomal Disorders and NEC 7 Intriguingly, there were 20 (16%) cases of NEC in the T21 cohort, but there were none in the T13 and T18 cohorts among neonates that survived ≥12 h after birth. These differences could be potentially explained by the significantly higher percentage of neonates with gestational ages <26 weeks in the T21 group (n = 22, 16%) than in the T18 group (n = 3, 3%); T13 was not significantly different (n = 2, 6%).…”
Section: Chromosomal Abnormalities Recorded In Infants With Necrotizi...mentioning
confidence: 99%
“…Other groups have focused on assessing the microbiota in the stool of patients with NEC [11], in a search for signature bacterial changes that can be readily assessed and which may provide clues to the onset of NEC development [64,65]. More recently, laboratories have focused on identifying various genetic risk factors for NEC [66], which has led to an understanding that polymorphisms in TLR4 associated genes, as well as others, may be linked to disease progression [30][31][32]. Finally, investigators are using more advanced diagnostic modalities including near-infrared spectroscopy to predict the course of NEC, and to identify its development at earlier stages based upon patterns of blood flow and tissue perfusion [67,68].…”
Section: New Diagnostic Approaches For Nec and The Bacterial-enterocymentioning
confidence: 99%